THE MALAISE AND SOLUTIONS: A RECURRENT THEME IN WALKER PERCY’S NOVELS - K. , N. Sharmila; T. , Deivasigamani (International Journal of Psychosocial Rehabilitation, 2020)
Walker Percy, the novelist of the American South, has written not only novels but treatises on language and morality also. His The Message in the Bottle is a book which deals with religious and philosophical aspects of human life. He is always concerned with the general, universal framework of moral standard which governs man’s everyday life. The individual spokes of human life lose their significance so far as they remain isolated from each other. Social order is possible only when the individuals are ready to patch up with the other, practicing what the Thunder said as quoted by T.S Eliot in the wasteland, namely ’Dalta,’ ’Daya-thuvam,’ and ’Damyutha,’ meaning ’Give,’ ’sympathize,’ and ’control. ’. This will take us back to the roots and weld the ’sundered soul together.’. All the ills, maladies, and malaise torturing human life will be remedied if ’togetherness’ and sharing of thoughts and feelings are practiced. Percy’s main idea is that a novelist has to warn society of the impending calamity lurking at every bend in the path of life. Walker Percy compares a novelist to a canary bird which gives warning cries to the miners who go down to the coal mines. His main concern is that it is his divine duty to diagnose the malaise afflicting the society and also to offer possible remedies to circumvent the impending calamities. It is further expounded in the present study.